(untitled) (Journal of Computational Mathematics, 2021)
High-attenuation object-induced streaking and shadow artifacts in computerized tomography (CT) are somewhat connected to the misfit of the X-ray projection data to the range space of the Radon transform. This misfit is mainly due to the beam hardening factor of the projection data which is unavoidable for polychromatic sources. The major difficulty in dealing with the beam hardening-induced streaking and shadow artifacts comes from its highly nonlinear nature depending on geometries of high attenuation objects. In this work, we investigate the mathematical characteristics of those streaking and shadow artifacts from the structure of the projection data. We also proposed a metal artifacts reduction method by incorporating the recent technique of the nonlinear beam-hardening corrector. Numerical simulations show that the proposed method effectively alleviates the streaking artifacts without changing the background images.